Experimental dielectronic recombination rate coefficients for Na-like S VI and Na-like Ar VIII - (:unkn) unknown (EDP SCIENCES S A, 2009)
Absolute recombination rate coefficients for two astrophysically relevant Na-like ions are presented. Methods. Recombination rate coefficients of S VI and Ar VIII are determined from merged-beam type experiments at the CRYRING electron cooler. Calculated rate coefficients are used to account for recombination into states that are field-ionized and therefore not detected in the experiment. Results. Dielectronic recombination rate coefficients were obtained over an energy range covering Delta n = 0 core excitations. For Na-like Ar a measurement was also performed over the Delta n = 1 type of resonances. In the low-energy part of the Ar VIII spectrum, enhancements of more than one order of magnitude are observed as compared to the calculated radiative recombination. The plasma recombination rate coefficients of the two Na-like ions are compared with calculated results from the literature. In the 10(3)-10(4) K range, large discrepancies are observed between calculated plasma rate coefficients and our data. At higher temperatures, above 105 K, in the case of both ions our data is 30% higher than two calculated plasma rate coefficients, other data from the literature having even lower values. Conclusions. Discrepancies below 104 K show that at such temperatures even state-of-the-art calculations yield plasma rate coefficients that have large uncertainties. The main reason for these uncertainties are the contributions from low-energy resonances, which are difficult to calculate accurately.
Keywords: atomic data; plasmas; Sun: corona; Sun: atoms; OPTICALLY THIN PLASMAS; FINITE-DENSITY PLASMAS; IONIZATION EQUILIBRIUM; IONS; RESONANCES; ELEMENTS